(untitled) (Vietnam Journal of Community Medicine, 2023)
Background: Diabetes is one of the most widespread endocrine disease with increasingly prevalence in developing countries. Kidney disorder is a frequent comorbidity in type 2 diabetic patients. In these patients, there are some particular characters that affect on treatment and prognosis. Verifying these factors can improve the result of treatment. Objectives: To describe the result of glycemia management in type 2 diabetes patients and kidney disorder treated in Vinh Phuc General Hospital in Vietnam, 2023. Methods: A cross-sectional study was performed on 123 type 2 patients diagnosed with diabetes and kidney disorder treated in Vinh Phuc general Hospital. Results: The average of patients age is 70,62 ± 9,62. Average duration of disease is 70,62 ± 9,62. The patienst was treated with insulin isolated is 76,4%. The propotion of target FBG on the first day and 90th is 35,8% and 42,3%. Moderate to good adherence by Morisky scale on the first and 90th elevated from 68,3% to 91,2%. Conclusions: Type 2 diabetic with kidney disorder in our sample seem to be more frequent in elderly population, have long duration of disease, mostly be treated with insulin isolated. The proportion of target FBG is low. Dietary patterns, physical activity, medication adherence get improve after intervention.